2012
DOI: 10.1007/s00415-012-6793-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral muscles are progressively affected in Duchenne muscular dystrophy: implications for dysphagia treatment

Abstract: Dysphagia is reported in advanced stages of Duchenne muscular dystrophy (DMD). The population of DMD is changing due to an increasing survival. We aimed to describe the dysphagia in consecutive stages and to assess the underlying mechanisms of dysphagia in DMD, in order to develop mechanism based recommendations for safe swallowing. In this cross-sectional study, participants were divided into: early and late ambulatory stage (AS, n = 6), early non-ambulatory stage (ENAS, n = 7), and late non-ambulatory stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 32 publications
2
78
0
Order By: Relevance
“…[15][16][17] Dysphagia with solids more than liquids has also been reported in DMD. [18][19][20][21][22] We identified similarly increased occurrence of dysphagia with solids, but did not detect progression of dysphagia with skeletal muscle weakness as reported in studies of DMD. 20,22 While the underlying pathology of dysphagia in dystroglycanopathy is unknown, surface EMG studies of swallowing in a small series of patients with DMD suggest that the muscles involved in swallowing are weak, with dysphagic DMD patients exerting a greater proportion of maximal Figure 3 Gastrointestinal symptoms in dystroglycanopathy (DG) relative to household controls…”
mentioning
confidence: 39%
“…[15][16][17] Dysphagia with solids more than liquids has also been reported in DMD. [18][19][20][21][22] We identified similarly increased occurrence of dysphagia with solids, but did not detect progression of dysphagia with skeletal muscle weakness as reported in studies of DMD. 20,22 While the underlying pathology of dysphagia in dystroglycanopathy is unknown, surface EMG studies of swallowing in a small series of patients with DMD suggest that the muscles involved in swallowing are weak, with dysphagic DMD patients exerting a greater proportion of maximal Figure 3 Gastrointestinal symptoms in dystroglycanopathy (DG) relative to household controls…”
mentioning
confidence: 39%
“…In addition, the TT of DMD patients, which increases in the advanced stages as previously reported, was proven to be greater than that of DM1 and ALS patients. 6 Although tongue atrophy in ALS patients might be related to tongue weakness, TT in muscular dystrophy, DMD and DM1 patients was not related to tongue strength. In particular, we found that "tongue pseudohypertrophy" in DMD patients had little relationship to tongue weakness (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…More recently, they reported again on the convenience and good reproducibility of quantitative muscle ultrasound to measure TT in DMD patients, but they only evaluated patients with muscular dystrophy. 6 In the present study, we not only measured patients with muscular dystrophy, but also those with ALS. In addition, the TT of DMD patients, which increases in the advanced stages as previously reported, was proven to be greater than that of DM1 and ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…35 patients from the cohort are still alive (aged 22-31 years); 18 died (aged [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Patients were ventilated by NIV (29/53) or IV (33/53).…”
Section: Causes Of Death and Ages Of Survival In Dmd What Is The Carmentioning
confidence: 99%